Optimalisasi OPTIMALISASI PERANAN ORANG TUA DALAM PENINGKATAN HAFALAN AL-QUR’AN ANAK DI STP KHOIRU UMMAH CIMAHI - Fitariani, Eva (Jurnal Empowerment, 2025)
Memorizing the Koran is not easy. Parents must be involved in guiding and motivating their children to memorize the Qur'an at home so that their memorization increases and becomes stronger. In some cases, parents simply hand over their children to teachers at school to guide them back. so that children are not too interested in memorizing the Koran. Thus, the goal of memorization is not achieved. This research aims to determine the role of parents in children's Al-Qur'an tahfiẓ education. This research uses a combination method, which means combining qualitative and quantitative methods. At the initial stage of the research, qualitative methods were used, and quantitative methods were used at the next stage. The method used to analyze the data was average score analysis. The results show that one indicator of the satisfaction category is the role of parents in increasing children's memorization of the Qur'an. This suggests that children see significant improvements in memorization as parents maximize this role, but a lack of self-confidence from parents causes children to memorize more slowly. Educators try to understand the role of parents in improving children's memorization of the Qur'an